Progressive and disabling lipoatrophy associated with insulin aspart via a continuous subcutaneous insulin infusion. (November 2015) - Boland, X; Chenoweth, H; Sulkin, T; Browne, D
Abstract: Since the advent of insulin analogues, the incidence of insulin‐induced lipoatrophy has been relatively rare save for a small number of isolated cases. We report a case of severe disfiguring lipoatrophy in an 18‐year‐old female patient following a change in the mode of administration of insulin aspart from subcutaneous injections to continuous subcutaneous insulin infusion (CSII). This case highlights the need for further research into the causes of insulin‐induced lipoatrophy and the need for caution when starting a patient on a CSII. Copyright © 2015 John Wiley & Sons.